(untitled) (El-Wahat Journal for Research and Studies, 2021)
This manuscript presents, Face recognition by combining different extraction approaches combining PCA (principal Component Analysis), DWT (Discrete wavelet transform) and neural networks. This method consists of four steps: i) Preprocessing, ii) Dimension reduction using DWT, iii) feature extraction using PCA and iv) classification using neural network. To validate this work, we have tested this technique on frontal images of the ORL and Yale databases. Keywords - Face Recognition, Biometrics, PCA, Neural Networks, Feature extraction, eigenfaces , DWT.